ANALISIS PENGARUH PELAKSANAAN GOOD CORPORATE GOVERNANCE DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN BUMN MANUFAKTUR YANG TERDAFTAR DI BEI - B11110017, Yopie WIJAYA (Jurnal Manajemen Update, 2014)
This study aimed to analyze the effect of the implementation of Good Corporate Governance (GCG) and financial performance to value of the firm on state-owned enterprises listed on the Indonesia Stock Exchange. The practice of Good Corporate Governance used in this study is the proportion of independent commissioner, while financial performance variables used in this study are current ratio, debt to equity ratio and return on assets. Object of this study is manufacture state-owned company that has been listed in Indonesia Stock Exchange. Samples used in this study were 11 companies with an observations period of 3 years by using purposive sampling method. This study used case study method. Data analyzed with test of classic assumption and examination of hypothesis with multiple linear regression method. The result of this study indicate that good corporate governance factor that represented by a variable number of independent commissioner has a positive significant effect to the value of the firm, the variable of current ratio has a negative effect to the value of the firm, the variable debt to equity ratio has no significant effect to the value of the firm, and the variable of return on assets has a positive significant effect to the value of the firm (Tobin’s Q) Keywords: Firm Value of The Company (Tobin’s Q), Good Corporate Governance, Independen Commisioner, Financial Performance, Current Ratio, Debt to Equity Ratio, and Return on Assets, Non financial State-Owned Company